WhatsApp Class: Establishing Students’ Writing Skill Through Feedback Activity in EFL Academic Writing Course - Yuniarti Yuniarti (Getsempena English Education Journal)
This study concerned with how students established groups’ feedback that support their cognitive presence. This study used a case study. Convenience samples were 15 students majoring in English language education department at the university of Muhammadiyah Aceh. Thematic analysis was used to examine the information from the written-based communication that were converted into Microsoft Word documents. The data was processed using NVivo software to code indicators emerged. Content analysis was used to analyse comments in the draft and final essays after feedback activities. The results of the feedback activity showed that the students attempted to construct cognitive presence in chats and written texts. In WhatsApp, the triggering, exploration phases appeared. The students did much integration phase by giving types of corrections on draft essays. Also, they did resolution phase by re-writing essays.  In the draft essays, the essays’ mistakes were 70.61%. In the final essays, the essays’ mistakes were 29.35%. The implication shows that collaboration via WhatsApp can be implemented to construct cognitive presence.